Cor Triatriatum Sinister in a French Bulldog. (11th July 2012) - Almeida, Gustavo L. G.; Almeida, Marcelo B.; Santos, Ana Carolina M.; Mattos, Ângela V.; Oliveira, Ludmila S. C.; Braga, Rômulo C.
Abstract : A 3-year-old male French Bulldog was evaluated due to recent history of intolerance to exercise and coughing. The clinical, radiographic, and echocardiographic findings were consistent with cor triatriatum sinister (CTS), a congenital heart anomaly in which the left atrium is subdivided into two compartments by an abnormal fibromuscular membrane. This defect has been rarely recognized in humans and in domestic cats. To the best of our knowledge, this is the first report of the disorder in the canine species.